دور ممارسات القيادة الاخلاقية في ادارة الازمات، دراسة استطلاعية لاراء عينة من موظفي المديرية العامة لكهرباء محافظة السليمانية - عبدالله, أمجد محمد (Sulaimani Journal for Humanities, 2022)
The research aims to identify the role of ethical leadership practices in crisis management, and the research community includes the employees of the General Directorate of Electricity of Sulaymaniyah Governorate, and (71) people were chosen as the research sample from administrators, heads of departments and people’s officials. Arithmetic, standard deviations, correlation coefficients, and simple regression coefficients), and the researcher used the descriptive analytical approach as he collected and analyzed data based on the questionnaire as a main tool for data collection in order to know the correlation and effect between the research variables. In light of the results of the research, the researcher concluded a set of conclusions, the most important of which is the existence of a moral correlation between ethical leadership practices and crisis management. The results of the research also show that ethical leadership practices have a significant impact on crisis management. Among the most important recommendations is the need to pay more attention to dealing with workers according to individual differences and to take more into account the human dimension, and the need to prepare a general guide to the tasks and powers of the administrative levels and employees, paying attention to job descriptions and defining authority and powers for all. Paying attention to advanced training programs that help the department to face crises in light of previous crises.